Utilization of Social Media Marketing Through Content on Instagram in Efforts to Improve the Brand Image of AK Riau Organic Chicken - Edrian Hasdimeyra (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the use of social media marketing through content on Instagram in an effort to improve the Brand Image of AK Riau Organic Chicken. This research uses a quantitative approach and is reinforced with qualitative data to enrich the analysis. The results of the research show that the use of Instagram in an effort to improve the brand image of AK Riau organic chicken, namely: 1) Good background design, color selection and layout ultimately creates a good psychological response to the brand image of AK Riau organic chicken. 2) Promotion. This is one of the activities that aims to influence consumers to know and understand the product or service so that interest in buying the goods or services arises, 3) consumer characteristics are factors that exist within a person and influence consumer behavior in purchasing a product. or services. Based on a consumer survey at AK Riau Organic Chicken, it can be explained that 55% of people got information about AK Riau Organic Chicken from Instagram media, 25% of people got information from other people and 20% of people got information from Facebook. 4) The level of attractiveness of the message. The attractiveness of the message that can be seen from the promotional activities of